KEPRIBADIAN DAN AKTUALISASI DIRI TOKOH UTAMA DALAM KUMPULAN CERPEN SEMUA UNTUK HINDIA KARYA IKSAKA BANU (KAJIAN PSIKOLOGI SASTRA) - AH Khuzaini (EDU-KATA, 2020)
His research was conducted with the aim to describe the personality and self-actualization of the main character in a collection of short stories all for Hindi iksaka banu (study) literary psychology. The data was collected using the reading method and recorded through qualitative research. Research findings show that. (1) The main figure of Dutch nationality who has a different personality from the Dutch in general towards the indigenous people (2) The conflict that was felt by the main character mostly started from a clash of principles with fellow Dutch citizens (3) The main character had great attention to the interests and goodness indigenous